Real-World Treatment Patterns in Men with Castration- Resistant Prostate Cancer Receiving Docetaxel - Keith L. Davis; Benjamin Gutierrez; Teresa Zyczynski; James A. Kaye (Journal of Health Economics and Outcomes Research)
**Background:** Docetaxel has been a standard of care for castration-resistant prostate cancer (CRPC) in the United States since 2004, yet little has been reported on its patterns of use in routine practice. To help understand these patterns, a retrospective study was conducted and is reported here.